Pengaruh Brand Personality, Brand Experience, dan Brand Love Terhadap Brand Loyalty (Studi pada Starbucks Sidoarjo) - Chariri, Mochammad Iqbal; Yani, Muhammad; Hariasih, Misti (Universitas Islam Kadiri, 2025)
This study aims to explore the influence of Brand Personality, Brand Experience, and Brand Love on Brand Loyalty at Starbucks Sidoarjo. The approach used in this research is quantitative with descriptive methods, involving all Starbucks customers in Sidoarjo as a population, and a sample of 100 people was taken. The sample selection was carried out using purposive sampling technique, with the criteria of men and women who were more than 17 years old and made direct purchases at Starbucks Sidoarjo outlets. Data were obtained through a questionnaire, and responses were rated using a Likert scale. To analyze the data, the PLS-SEM method was applied with the help of SmartPLS 3. 0 software. The findings of this study indicate that Brand Personality has an effect on Brand Loyalty of Starbucks products in Sidoarjo, Brand Experience also contributes to Brand Loyalty of Starbucks products in Sidoarjo, and Brand Love has an influence on Brand Loyalty of Starbucks products in Sidoarjo.